Marine issues: from a scientific, political and legal perspective - Ehlers, Peter; Wolfrum, Rüdiger; Mann-Borgese, Elisabeth (Kluwer Law International, 2002)
The purpose of the papers in this volume is to enhance awareness of the European public, governments, the private sector and academia about the importance of responsible ocean and coastal management based on ocean science